2012
DOI: 10.1039/c2cp22231k
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the molecular channel in acetaldehyde photodissociation: roaming and transition state mechanisms

Abstract: The roaming dynamics in the photodissociation of acetaldehyde is studied through the first absorption band, in the wavelength interval ranging from 230 nm to 325 nm. Using a combination of the velocity-map imaging technique and rotational resonance enhanced multiphoton ionization (REMPI) spectroscopy of the CO fragment, the branching ratio between the canonical transition state and roaming dissociation mechanisms is obtained at each of the photolysis wavelengths studied. Upon one photon absorption, the molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
63
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 66 publications
7
63
1
Order By: Relevance
“…The theoretical fit was used to infer that the major route via roaming pathway accounts for 84% ± 10% of the total CH 4 +CO products, 5 showing a substantial deviation from the previous values. 6,8 Until a recent study, 4 Kable and co-workers reconciled the inconsistent results by probing CO with (2 + 1) REMPI ion-imaging in the wavelength range of 308-328 nm. They demonstrated that the low-J, a low speed component of the CO bimodality, results from roaming of a H-atom about a CH 3 CO core, while the high-J, a fast speed component, arises from a second roaming of CH 3 around CHO.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The theoretical fit was used to infer that the major route via roaming pathway accounts for 84% ± 10% of the total CH 4 +CO products, 5 showing a substantial deviation from the previous values. 6,8 Until a recent study, 4 Kable and co-workers reconciled the inconsistent results by probing CO with (2 + 1) REMPI ion-imaging in the wavelength range of 308-328 nm. They demonstrated that the low-J, a low speed component of the CO bimodality, results from roaming of a H-atom about a CH 3 CO core, while the high-J, a fast speed component, arises from a second roaming of CH 3 around CHO.…”
mentioning
confidence: 99%
“…At the same wavelength, Bañares and co-workers analyzed the kinetic energy distribution of the CO fragment acquired by resonance-enhanced multiphoton ionization spectroscopy (REMPI) coupled with ion-imaging and obtained a roaming branching to be 20%. 8 In a combined experimental and theoretical study, Heazlewood et al obtained the CH 4 product with highly vibrationally excited states, which was predicted consistently by quasi-classical trajectory (QCT) calculations. The theoretical fit was used to infer that the major route via roaming pathway accounts for 84% ± 10% of the total CH 4 +CO products, 5 showing a substantial deviation from the previous values.…”
mentioning
confidence: 99%
See 3 more Smart Citations